Structural and functional modeling of protein in cumin (Cuminum cyminum) - JETHRA, GEETIKA; CHOUDHARY, SHARDA; SINGH, PRIYANKA; ADWANY, SHWETA; PANWAR, ALKA (The Indian Journal of Agricultural Sciences, 2015)
Emergence of in-silico techniques have revolutionized the traditional methods of protein structure and function prediction of proteins. These computational tools encouraged the development of protein models in cumin (Cuminum cyminum L.) and have opened up new vistas in the area of research. In the present study, a high quality 3D structure and function of cumin RZ 19 protein have been predicted for the hypothetical amino acid sequence which showed homology with the protein domain of humans and E. coli illustrating that the database available on Apiaceae family is very low. The estimated molecular weight of identified cumin RZ 19 protein was 55028.6 and was predicted as an acidic protein with pI 5.14. Its functions are broadly classified into 2 categories: 1) Biological process: oxidationreduction and ion transport with a probability of 98.9% and 97.8% respectively and 2) Molecular function: structural constituent of ribosome with 99.0% and oxidoreductase activity with 98.7% probability. We have also identified a channel in cumin transmembrane protein, through which a ligand (an ion or a small molecule) might pass. The present finding may be a valuable addition to the proteomic information available on cumin. Further validation can be performed using wet lab experiments.